2013
DOI: 10.1063/1.4809657
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of ultrathin Fe films in MgO/Fe/MgO in epitaxial structures probed by nuclear resonant scattering of synchrotron radiation

Abstract: Nuclear resonant scattering (NRS) of synchrotron radiation was used to investigate the magnetic anisotropy of iron films in MgO/Fe(t)/MgO(001) structures for t = (4–10) Å. The low-temperature NRS spectra were analyzed using a static magnetization model involving two interface-like components and a bulk-like component. We confirmed the existence of perpendicular magnetic anisotropy in MgO/Fe/MgO structures at 10 K with an increasing in-plane component of the magnetization for t > 8 Å over the entire thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…In the case that the fluctuation rate of the magnetization direction due to superparamgnetic relaxation is higher than the Larmor precession rate of Fe nuclei, the hyperfine field averages out to zero [41]. The presence of superparamagnetic relaxation in thin films of Fe on MgO has also been seen in some earlier NRS and CEMS studies [10,25]. At a thickness of 2.0 nm, the film exhibits a finite hyperfine field.…”
Section: B Ginrs Studymentioning
confidence: 56%
See 2 more Smart Citations
“…In the case that the fluctuation rate of the magnetization direction due to superparamgnetic relaxation is higher than the Larmor precession rate of Fe nuclei, the hyperfine field averages out to zero [41]. The presence of superparamagnetic relaxation in thin films of Fe on MgO has also been seen in some earlier NRS and CEMS studies [10,25]. At a thickness of 2.0 nm, the film exhibits a finite hyperfine field.…”
Section: B Ginrs Studymentioning
confidence: 56%
“…Interfacial imperfections in terms of possible oxidation of transition metal in the interfacial region or oxygen vacancies, etc., are suggested to be possible reasons for deterioration in TMR value [3][4][5]. This has led to extensive study in the literature on characterization of interfaces in MgO based MTJs [6][7][8][9][10][11]. However, understanding of various interfacial imperfections and their correlation with magnetic and magneto-transport properties of magnetic electrodes is still far from satisfactory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrathin Fe(001) films embedded between the MgO(001), with thicknesses below the critical value necessary to establish perpendicular magnetization [15,16], are superparamagnetic at RT, as indicated in Fig. 2 is characterized by a typical broadening that reveals that the ferromagnetic order is averaged out because of random jumps in the magnetization of the superparamagnetic particles.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have demonstrated that iron in epitaxial MgO/Fe/MgO trilayers grown on MgO(001) has perpendicular anisotropy below a certain critical Fe thickness [15,16]; however, because of the cluster growth, superparamagnetism significantly influences the magnetic properties of MgO/Fe/MgO at room temperature (RT). Simultaneously, granular Fe/MgO multilayers fabricated on amorphous [13,17] and single-crystal substrates [18] have been optimized for maximum tunneling magnetoresistance (TMR) and field sensitivity at RT.…”
Section: Introductionmentioning
confidence: 99%